Intracardiac Porcupine Quill Migration in a Dog: Multimodality Imaging Findings and Surgical Management - Antonello Bufalari; Giulia Moretti; Eleonora Monti; Lisa Garofanini; Giovanni Angeli; Francesco Porciello; Maria Chiara Marchesi; Domenico Caivano (Veterinary Sciences, 2022)
The porcupine is a nocturnal quill-bearing rodent common throughout Italy. When threatened, it defends itself by erecting its quills, rattling its tail, and running sideways or backyard into predators. The quills are released upon contact with assailants and tend to migrate into several body tissues or cavities due to the unique inverted cuticles (crenate) directed downwards to the quill base (a sort of “harpoon effect”). Intracardiac migration of porcupine quills has been reported in a few dogs with severe clinical signs. This case report describes a single porcupine quill [Hystrix cristata, (HC)] migration through the heart in a dog and the use of multimodality imaging for the diagnosis and surgical approach. A 4-year-old 25 kg female mixed-breed dog was presented for evaluation of recurrent fever. Transthoracic echocardiographic examination showed a linear, hyperechoic foreign body traversing the interventricular septum from the heart base to the cardiac apex. Computed tomography and transesophageal echocardiography confirmed the presence of a single structure resembling a quill; a later esophageal endoscopy showed no anatomical alterations or mucosal injuries. Following median sternotomy and after accurate localization by intraoperative ultrasound, the quill was successfully removed. The dog had a good recovery without evidence of severe cardiac injury secondary to an intracardiac quill. To the best of the authors’ knowledge, the identification of an intracardiac HC quill by ultrasonography and CT and its successful removal by ultrasound guide has not been previously reported.